The Application of Encapsulated Gluten on Tapioca Wet Noodle Making Processing - Husniati, Husniati; Nurdjanah, Siti; Prakasa, Ryan (Biopropal Industri, 2015)
Gluten is a specific protein found in wheat and functionally needed to improve its elasticity and texture of carbohydrate-based dough. Gluten, isolated from wheat, can be used in the free-form or encapsulation. The aim of this research was to investigate the effects of encapsulated gluten addition on properties of tapioca for wet noodle production. The parameters studied were texture, sensory, and pasting properties of the noodles. The ratios of encapsulated gluten to tapioca were 97%:3%, 96%:4% and 95%:5%. The results showed that the use of encapsulated gluten as much as 3% w/w gave the best noodle with the characteristics of setback viscosity, low cooking loss and organoleptically preferred by panelists.